THE IMPACT OF SELF-CARE MANAGEMENT IMPLEMENTATION ON QUALITY OF LIFE IN INDIVIDUALS WITH TYPE 2 DIABETES - Ismi Irfiyanti Fachruddin; Anwar Lubis (Jurnal Gizi dan Pangan Soedirman, 2026)
Type 2 Diabetes Mellitus (T2DM) is a non-communicable disease that is becoming widespread worldwide, particularly in Indonesia. This illness might diminish patients' quality of life due to complications and treatment challenges. A crucial approach in the management of type 2 diabetes mellitus is self-care management, which includes food restriction, physical activity, blood glucose monitoring, medication adherence, and foot care. This study is to examine the correlation between self-care management practices and the quality of life in persons with type 2 diabetes mellitus. The study used a cross-sectional design with 58 individuals in the Chronic Disease Management Program (Prolanis) at Fauziah Clinic, Makassar. The instruments used included the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire for evaluating self-care behaviour and the Diabetes Quality of Life (DQOL) instrument for assessing patients' quality of life. The results revealed that 55.2% of individuals demonstrated proficient self-care management, whereas 56.9% assessed their quality of life as excellent. Bivariate analysis demonstrated a significant association between self-care management and quality of life (p-value = 0.005). This study suggests that proficient self-care management significantly improves the quality of life for individuals with type 2 diabetes mellitus. Health education, familial support, and consistent monitoring services are crucial for enhancing patient compliance with self-management.